Correlations between biofuels and related commodities: A taxonomy perspective - Ladislav Krištoufek; Karel Janda; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2012)
In this paper, we analyze the relationships between the prices of biodiesel, ethanol and related fuels and agricultural commodities with a use of minimal spanning trees and hierarchical trees. We find that in short-term, both ethanol and biodiesel are very weakly connected with the other commodities. In medium-term, the biofuels network becomes more structured. The system splits into two well separated branches - a fuels part and a food part. Biodiesel tends to the fuels branch and ethanol to the food branch. When the periods before and after the food crisis of 2007/2008 are compared, the connections are much stronger for the post-crisis period. This is the first application of this methodology on the biofuels systems.
Keywords: C38; Q16; Q42; 330; biofuels; networks; minimal spanning tree; hierarchical tree